Analisa Kekuatan Tali Baja Sling Crane Berkapasitas 40,6 Ton Di PT. Pelindo IV (Persero) Kendari - Ashbah, Ashbah; Mangalla, Lukas Kano; Aksar, Prinob (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2023)
At the port usually the tools used as moving goods are container cranes, container cranes have the main component of steel rope slings which function as lifting cables on the hoist, usually chosen according to the needs of a construction for that it is necessary to analyze the strength of the steel rope slings currently used and comparing the steel rope with other types of steel rope in order to obtain a more comprehensive understanding of alternative steel rope selection that is appropriate for use in container/container lifting mechanisms. Research Objectives To analyze and determine the strength of a sling crane steel rope with a capacity of 40.6 tons and to determine the electrical power used. The research method is to make observations to determine the length of the steel rope using a roll meter and the diameter of the steel rope using a caliper. research, namely the calculation on wire rope obtained 3,896, kg, the cross-sectional area of the steel rope is 615.44 mm², the breaking stress is 6,330 kg/mm², the permissible breaking load of the steel rope is 12,150 kg, the tensile stress on the steel rope is 2,518 kg, the calculation on driving machine The resulting power (N) is 40.21 kW, the moment of static resistance on the motor shaft (M) is 239.927 kg.m.Keywords: Container, crane, steel rope, container